Detecting the relations between meteorological elements and alpha and beta activity concentration at Al-Tuwaitha site, Baghdad - Salwa S. Naif; Thoalfaqar Al-Rbayee; Monim H. Al-Jiboori (Przegląd Naukowy Inżynieria i Kształtowanie Środowiska, 2021)

(untitled)
In this study, 50 samples of air particulates collected from different places in- and outside the Al-Tuwaitha nuclear site, south of Baghdad were used to measure daily gross alpha and beta activity concentrations (AAC and BAC) for the period from 28 January 2015 to 13 April 2017. At the same time, several meteorological factors such as air temperature, wind speed, wind direction, air pressure, relative humidity, and solar radiation, were also measured. Air stability classes were also derived from wind speed and solar radiation. AAC/BAC variations in the surface air layer were discussed in relation to these factors. The results show that there are inverse relations between AAC/BAC and wind speed and temperature, linear relations between AAC/ABC and air pressure and weak relations between AAC/BAC and relative humidity and solar radiation. Lastly, AAC/BAC measurements in unstable air are as large as in neutral air.